PHILOSOPHY OF MIND AND COGNITIVE SCIENCE AS AN IDEA IN MACEDONIA (Annual of the Faculty of Philosophy in Skopje, 2016)
The article discusses some key concepts and problems in contemporary philosophy mind and cognitive science: concept of naturalism, intertheoretic reduction, functionalism and supervenience. An overview is given on reception and future of the philosophy of mind in Macedonia.